PENCAHAYAAN RUANG ARSITEKTUR DENGAN FIBER OPTIC SEBAGAI ALTERNATIF PENCAHAYAAN ALAMI DAN PEMANFAATAN ENERGI TERBARUKAN - Anggoro, Suryo (BPPT)
Natural daylighting methods for building commonly used windows and facade openings to let sunlight inside the interior of building. Hence, light quality received sometimes inadequate and unoptimal which caused natural lighting being replaced by artifi cial (electric) lighting that lead into dependency of electrical lighting. Fiber optic has a capability of transmitting optical wave including sunlight which already collected throught concentrating sunlight collector. Through fi ber optic sunlight transmitted inside building with better intensity and improved quality than artifi cial produced light.Key words: daylighting, fi ber optic